Biological evaluation of coagulation problems in COVID-19 patients hospitalized at the centre hospitalier mère-enfant monkole, kinshasa, Democratic Republic of the Congo - Merlin Matena; Gédéon N. Bongo; Honoré Ngbanda; Eddy B. Bakemo; Yves M. Mukaba; Jossard K. Munzumba; Justin M. Vuvu; Christel K. Kande; Jacques N. Ngayuna; Jonathan I. Kukila; Ngbolua Koto-te-Nyiwa (Medical Laboratory Journal, 2023)
Background: COVID-19 is a viral infection caused by SARS-CoV-2, which enters the body via the ACE2 receptor. This study aims to evaluate the coagulation disorders of COVID-19 patients admitted to Centre Hospitalier Mère-Enfant Monkole, Kinshasa. Methods: This descriptive cross-sectional hospital-based study of patient files was conducted between July 2020 and June 2021 at CHME-Monkole in Kinshasa. The sample size was 130 patients using a random sampling technique after interviewing the respondents. For each respondent, biological and socio-demographic data were collected on a questionnaire. The primary analyses included the determination of PT, APTT, Plasma determination of D-dimers, and platelet count. A descriptive analysis was performed for socio-demographic characteristics, while Pearson correlation was used to determine the associations between socio-demographic characteristics and different biological parameters using SPSS 25.0. For ethical reasons, informed consent from patients was sought, and confidentiality was assured. The authorization was provided by the Ethical Committee of CHME-Monkole (Ethical code: KIN/CHME/04/2020). Results: The findings showed D-dimer levels higher than 500 µg/L in 87.7% of respondents, prolonged APTT (>40 seconds) in 43.1% of respondents, PT (<70%) in 36.9% of respondents, and thrombocytopenia (platelets <150,000) in 26.2% of respondents. A positive correlation was observed between socio-demographic characteristics and D-dimer levels. Conclusion: SARS-CoV-2 infection has a significant impact on coagulation. Thus, determining these biomarkers could predict the risk of disease severity or death in patients with COVID-19.